Climate Change Impacts on Zooplankton Phenology and Migration Patterns in Rajasthan: A Mechanistic Modeling Approach (International Journal of Food and Nutritional Sciences, 2023)
With changes in temperature, salinity, and hydrological cycles, among other environmental factors, climate change is dramatically affecting the phenology and migration patterns of zooplankton, which is an important organism in aquatic ecosystems. Rising global temperatures and changing precipitation regimes are having an adverse effect on zooplankton phenology, which controls the timing of vital life events like feeding and reproduction, as well as their vertical or horizontal migration patterns. In order to comprehend these effects, a mechanistic modeling approach is discussed in this review. It focuses on freshwater and marine ecosystems, with particular attention to freshwater zooplankton in areas such as Rajasthan. Mechanistic models use temperature-driven growth and metabolic models, hydrological models, and ecosystem models to predict changes in zooplankton dynamics. These models mimic the physiological reactions of zooplankton to environmental changes. The findings point to potential mismatches between zooplankton and their main food sources, such as phytoplankton, as well as earlier seasonal blooms and higher metabolic rates. These factors could have a domino effect on aquatic food webs. The effects of climate change are exacerbated in shallow freshwater systems, like those in Rajasthan, by increasing salinity, less water available, and unpredictable monsoons that change the habitat and dispersal patterns of zooplankton.This study offers insights into how zooplankton communities will be impacted by climate-driven environmental changes through mechanistic modeling, with broad implications for ecosystem services, biodiversity, and fisheries management. Nonetheless, there are still unknowns, particularly in areas with limited data, which calls for more field research to improve models and forecasts of the long-term effects of climate change on zooplankton populations.